2018
DOI: 10.1021/acsnano.8b01001
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Janus Mesh: Underwater Bubble Antibuoyancy Unidirectional Penetration

Abstract: Gas bubbles are a powerful tool with applications in particle visualization, spacers, actuation pistons, and pressure sensors. Controlling the transportation of bubbles in the liquid phase is a challenge that needs to be solved in many industrial processes, such as in the pipe transportation of fluids, the corrosion of ocean vessels, and the control of foaming processes. There are few existing materials capable of the antibuoyancy unidirectional transportation of bubbles. Here, a Janus superwetting mesh is fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 36 publications
0
80
0
Order By: Relevance
“…Two‐layer compositing is a common way for the asymmetric fabrication. For example, oppositely wettable metal meshes [ 16–20 ] or porous anodic alumina [ 21 ] membranes are directly integrated into a Janus membrane. Layer‐by‐layer electrospinning is able to establish a two‐layered Janus nanofibrous membrane by sequentially electrospinning hydrophobic nanofibers onto hydrophilic ones and vice versa.…”
Section: Asymmetric Surface Construction and Regulation For Janus Memmentioning
confidence: 99%
See 2 more Smart Citations
“…Two‐layer compositing is a common way for the asymmetric fabrication. For example, oppositely wettable metal meshes [ 16–20 ] or porous anodic alumina [ 21 ] membranes are directly integrated into a Janus membrane. Layer‐by‐layer electrospinning is able to establish a two‐layered Janus nanofibrous membrane by sequentially electrospinning hydrophobic nanofibers onto hydrophilic ones and vice versa.…”
Section: Asymmetric Surface Construction and Regulation For Janus Memmentioning
confidence: 99%
“…The asymmetric pore size configuration can also be realized via bonding two membrane layers with different pore sizes. For example, directly integrating two meshes with different pore sizes is a facile way to construct asymmetric pores, [ 17,18,20 ] but the porosity would be reduced to some extent due to the mismatching of pores at the interface. Moreover, electrospinning is able to control the pore size of nanofibrous membranes through changing the concentration of electrospinning liquid or electrospinning parameters such as needle size, electric field intensity, and operation time.…”
Section: Asymmetric Surface Construction and Regulation For Janus Memmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 ] The concept of directional permeability was first introduced in 2010 and has attracted considerable attention in membrane research in recent years. [ 4–16 ] The main idea of directional permeability is to achieve a novel separation performance by having two layers of opposite capabilities. The application of Janus membranes is mainly concentrated in the field of oil–water separation, and they are expected to become a new candidate to replace traditional separation membranes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5–7 ] In recent years, Janus membranes have been extensively applied to battery diaphragms, [ 8–10 ] water collection, [ 11–13 ] and ultra‐fine bubbling. [ 14–16 ] Jiang et al [ 2 ] conducted an in‐depth study on the principle of directional permeation in porous Janus membranes and found that when the hydrophobic layer was placed at the top of the membrane, water easily passed through membrane layers; however, when the hydrophilic layer was placed at the top, water only spread over the membrane surface. When Janus membrane is properly designed, the presence of micropores cannot cause the penetration of water.…”
Section: Introductionmentioning
confidence: 99%